Unusual cardiac manifestation of Hepatitis A virus infection in children – A case report - Afreen Khan,; Aparna Chakravarty,; Jagannath Mohapatra, (Indian Journal of Child Health, 2020)
Hepatitis A virus infection is one of the major causes for acute viral hepatitis in children. Many extra-hepatic manifestations have been described in the literature. Only three cases of cardiovascular involvement in Hepatitis A in children have been reported till now. We here report two pediatric case of Hepatitis A infection with bradycardia.